Case report: A challenging case of severe Cushing’s syndrome in the course of metastatic thymic neuroendocrine carcinoma with a synchronous adrenal tumor - Dzialach, Lukasz; Wojciechowska-Luzniak, Agnieszka; Maksymowicz, Maria; Witek, Przemysław (Frontiers in Endocrinology, 2024)
Ectopic ACTH syndrome (EAS) remains one of the most demanding diagnostic and therapeutic challenges for endocrinologists. Thymic neuroendocrine tumors account for 5%–10% of all EAS cases. We report a unique case of a 31-year-old woman with severe EAS caused by primary metastatic combined large-cell neuroendocrine carcinoma and atypical carcinoid of the thymus. The patient presented with severe hypercortisolemia, which was successfully controlled with continuous etomidate infusion. Complex imaging initially failed to detect thymic lesion; however, it revealed a large, inhomogeneous, metabolically active left adrenal mass infiltrating the diaphragm, suspected of primary disease origin. The patient underwent unilateral adrenalectomy, which resulted in hypercortisolemia resolve. The pathology report showed an adenoma with adrenal infarction and necrosis. The thymic tumor was eventually revealed a few weeks later on follow-up imaging studies. Due to local invasion and rapid progression, only partial resection of the thymic tumor was possible, and the patient was started on radio- and chemotherapy.